Os documentários musicais brasileiros : uma análise do filme Nelson Freire - Amaral, Guilherme Gustav Stolzel (Universidade Federal de São Carlos, 2015)
This dissertation aims to analyze the documentary Nelson Freire seeking to explore the main aspects that distinguish this work from most of the musical documentaries made in Brazil between the years of 2000 and 2013. The peculiarities of Nelson Freire were detected and problematized establishing a dialogue between the film and three of the major trends that integrate the contemporary Brazilian scene of documentaries about music: the trend of record of intimacy and the everyday life, the trend of musical performance, and the biographical trend.
Keywords: Nelson Freire; Documentário musical; Registro da intimidade; Registro do cotidiano; Performance musical; Nelson Freire; Musical documentary; Record of intimacy; Record of the everyday life; Musical performance; Biography; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA